RECENT STUDIES ON BACTERIAL POPULATIONS AND PROCESSES IN SUBSEAFLOOR SEDIMENTS: A REVIEW - Parkes R.J.; Cragg B.A.; Wellsbury P. (My University, 2002)
Subsurface bacteria also occur in hydrothermal sediments with large temperature gradients (up to 12 °C/m) and with population numbers similar to non-hydrothermal sites at temperatures from psychrophilic to mesophilic. At greater depths and temperatures, populations decline rapidly, but they are still significant up to hyperthermophilic temperatures and are even stimulated by subsurface seawater flow. These results suggest that temperature alone does not limit bacteria in non-hydrothermal sediments until about 4 km, and evidence exists that bacterial processes may even be sustained by interaction with thermogenic processes as temperatures increase during deep burial. Experiments demonstrate that in the presence of readily degradable organic substrates, actively growing bacteria can move faster than sediment deposition; hence, these bacteria are not necessarily trapped and buried. However, bacterial growth decreases with depth to such an extent that subsurface bacteria would not be able to keep up with sedimentation rate and hence would be buried. In some circumstances, such as in sapropel layers with high organic matter in the Mediterranean, bacteria may be buried within a specific deposition horizon. Subsurface bacteria can utilize old and recalcitrant organic matter, but only very slowly, and they seem to have a strategy of high biomass and low growth rate, commensurate with their geological habitat of generally low energy flux.
Keywords: microbial processes; subseafloor sediments; bacteria